Can encroached rangelands enhance carbon sequestration in the African Savannah? - Mudereri, Bester Tawona; Chitata, Tavengwa; Musekiwa, Nyasha B; Angombe, Simon T; Kambatuku, Jack (Elsevier, 2022)
Climate change and bush encroachment pose huge challenges to rangeland management in Namibia. These challenges require a holistic management approach that ensures consistent and optimum forage productivity and sustainability. Mechanical and chemical control methods are the most used techniques in controlling woody encroaching species to improve pastoral properties in the Namibian savannas. However, there is very little in- formation regarding the management options that concurrently solve climate change and bush encroachment problems. This study compares the effects of different bush encroachment control methods -chemical control and mechanical control using a restoration thinning strategy and chemical aftercare- on carbon stocks, carbon sequestration and social cost of carbon on two farms in the Otjozondjupa region of Namibia. Allometric equations were evaluated and used to estimate carbon stocks. Carbon sequestration was estimated from the carbon stocks using the ratio of atomic masses of C and CO2 while the social cost was assumed at the published rate of $56.00 per ton of carbon. Results show that AGB estimates from the species and country-specific allometric equation for Senegalia mellifera (R2 0.86; se 0.063), Dichrostachys cinerea (R2 = 0.77; se = 0.076), Senegalia fleckii (R2 =0.83; se = 0.148), Senegalia erubescens (R2 = 0.81; se = 0.519) and Vachellia reficiens (R2 =0.81; se =0.519) were highly correlated to the measured ABG. Therefore, the species and country-specific allometric equations are good predictors of AGB in the study site. The generic equation Y = Exp [-2.187+0.916ln(X2 x WD x H)] used to es- timate AGB for Acacia erioloba, Grewia flavescens, Grewia bicolar was moderately strong ranging from R2 = 0.46 to R2 = 0.55. The generic allometric equation overestimated the ABG for Acacia erioloba by 22.4% and under- estimated ABG for Grewia bicolar by 32.3% and 19.8%, respectively. Results indicate a significant difference between the mechanical and chemical control methods in both carbon stocks and carbon sequestration; p = < 0.001 and p = < 0.001, respectively. The carbon sequestration for the control plot was 331 t/ha, which is 58% and 61% higher than the carbon sequestered in the mechanically and chemically treated plots, respectively. The mechanically treated plots sequestered 137.95 C, 7.5% more carbon dioxide than the chemically treated plots. The net value of carbon sequestration was highest in the control treatment (US$18,536.68), followed by me- chanically treated plots (US$7,725.49), which is 7% higher than chemically treated plots (US$7,147.98). The mechanical control method - restoration thinning and chemical aftercare- performs better in climate mitigation based on carbon sequestration. However, climate change and rangeland management should consider the high contribution of woody encroached areas to carbon sequestration. Our findings point to a C sequestration-based approach to making rangeland management decisions, an approach valuable in holistic climate change miti- gation and forage improvement.